2013
DOI: 10.1038/cddis.2013.214
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to TRAIL in non-transformed cells is due to multiple redundant pathways

Abstract: Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) is a cytokine and a selective inducer of apoptosis in a range of tumour cells, but not in normal, untransformed cells. A large number of chemotherapeutics as well as biological agents are being tested for their potential to sensitise resistant tumour cells to TRAIL as a means to broaden the range of tumours treatable with TRAIL. However, because of the incomplete understanding of the mechanism(s) underlying TRAIL resistance in non-malignant cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 58 publications
1
56
0
Order By: Relevance
“…However, the mechanism(s) that lead to normal cell TRAIL resistance have yet to be fully characterized. Van Dijk et al (37) have previously investigated TRAIL resistance in non-transformed primary dermal fibroblasts and umbilical artery smooth muscle cells. They found that multiple pathways control TRAIL resistance in normal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism(s) that lead to normal cell TRAIL resistance have yet to be fully characterized. Van Dijk et al (37) have previously investigated TRAIL resistance in non-transformed primary dermal fibroblasts and umbilical artery smooth muscle cells. They found that multiple pathways control TRAIL resistance in normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…They found that multiple pathways control TRAIL resistance in normal cells. c-FLIP, Bcl-2, and X-linked inhibitor of apoptosis protein have all been found to provide resistance to normal cells and act in a redundant manner (37).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] For example, DcR1 was found to be the strongest single predictor of overall survival in AML 17 and in vitro overexpression of DcRs protected tumour cells from TRAIL-induced apoptosis. On the contrary, DcR expression in the tumour does not correlate with TRAIL sensitivity 18,19 and non-transformed cells do not require DcRs to be protected from TRAIL-induced apoptosis, 20 suggesting that the in vivo role of the DcRs may be more complex than originally thought. In this study, we examined the hypothesis that DcRs exert a 'tissue-level control' of TRAIL sensitivity rather than simply regulating TRAIL resistance at a cell autonomous level.…”
Section: Introductionmentioning
confidence: 92%
“…Cells were harvested by centrifugation, lysed, denatured and proteins separated and blotted as described before [6]. Blots were incubated with rabbit polyclonal antibodies against caspase-3 (1:1 000; Cell Signaling Technologies, Danvers, MA, USA), Mcl-1 (1:1 000; Cell Signaling Technologies), Cyclin E (1:1 000, Sigma), Cyclin B1 (1:1 000, ThermoScientific),or actin (1:500; Sigma) and mouse monoclonal antibodies against caspase-8 1C12 ( …”
Section: Western Blot Analysismentioning
confidence: 99%
“…Recent studies however identified drug combination strategies that could potently sensitize TRAIL-resistant tumours [6]. Additionally, a recent study on acute lymphocytic leukemia has shown that the undifferentiated leukemiainitiating cell (LIC) population is sensitive to TRAIL and tumour extracts from TRAIL-treated xenografts fail to re-establish the tumour when transplanted into a new animal [7] highlighting the possible potential of TRAIL for targeting the undifferentiated cells driving erythroid leukemia.…”
Section: Introductionmentioning
confidence: 99%